Os obstáculos ao desenvolvimento na obra de Celso Furtado em dois momentos: a fase pré 64 e o milagre econômico - Bonafin, Téssio Roberto Rissi (2012)
The purpose of the dissertation is to analyse the Brazilian development in the Twentieth Century beyond Celso Furtado work. The paper utilizes of two historical Brazilian moments, and the Cold War as a background, conditions that gave to Furtado the chance to create theories to explain the limits of development in peripheral nations, according the Center Periphery Theory, also in the dissertation. Divided two moments of analyses in the Brazilian history, the first one before the Military Coup in 1964, and the second in later years , we seek to know what Furtado positions in his work, in selected books. To answer the question, why Brazil, and other nations outside the Center, didn´t get, or don´t get a similar development as the countries considered rich, in Celso Furtado vision, is one of the goals of the research, among the future comparison of his arguments and theories in both historical periods.